Prognostic performance of qSOFA in oncology patients admitted to the emergency department with suspected infection. Issue 1 (20th October 2020) - Koh, Tze Lui; Canet, Emmanuel; Amjad, Sobia; Bellomo, Rinaldo; Taylor, David; Gan, Hui K.; Marhoon, Nada; Lim, Andrew; Ong, Wee Loon; Krishnan, Vivek; Khor, Richard
Abstract: Aim: We aimed to test the performance of the quick Sequential Organ Failure Assessment score (qSOFA) in predicting the outcomes of oncology patients admitted to the emergency department (ED) with suspected infection. Methods: Retrospective cohort analysis of all oncology patients presenting to the ED of a tertiary hospital with suspected infection from 1 December 2014 to 1 June 2017. Patients were identified by cross‐linkage of ED and Oncology electronic health records. The primary outcome was in‐hospital mortality and/or ICU stay ≥ 3 days. Results: A total of 1655 patients were included in this study––1267 (76.6%) with solid tumor and 388 (23.4%) with hematological malignancies. At presentation, 495 patients had chemotherapy, and 140 had radiotherapy within the preceding 6 months. Four hundred patients received chemotherapy and/or radiotherapy in the previous 4 weeks. Overall, 371 (22.4%) patients had qSOFA ≥ 2. Such patients had a higher likelihood of respiratory infections compared to patients with a qSOFA < 2 (43.9% vs 29%) and were more likely to be admitted to ICU or require mechanical ventilation. In‐hospital mortality or in‐hospital mortality and/or ICU stay ≥ 3 days were 17.3% and 21%, for qSOFA ≥ 2 patients versus 4.7% and 6.9% for qSOFA < 2 patients ( P < .001). qSOFA ≥ 2 had a negative predictive value of 95% for in‐hospital mortality and 93% for in‐hospital mortality or ICU stay ≥ 3 days. Conclusion: Among oncology patients presenting to the ED with suspected infection, a qSOFA ≥ 2 is associated with a threefold risk of hospital mortality/prolonged ICU stay. Its absence helps identify low‐risk patients.